Current Practices of Adjunctive Therapy for Pertussis at Six Canadian Tertiary Care Pediatric Hospitals - Christopher T Naugler; Scott A Halperin (Canadian Journal of Infectious Diseases)
OBJECTIVE: To document initial investigations and treatment used in the management of children hospitalized with pertussis.